PENGARUH EMPLOYER BRANDING DAN WORK LIFE BALANCE TERHADAP TURNOVER INTENTION PADA GENERASI Z DI KOTA MEDAN: JOB SATISFACTION SEBAGAI VARIABEL INTERVENING - Sihotang, Helena; Sitompul, Pandapotan (UNIKA Santo Thomas, 2024)
This study was conducted to determine how the influence of Employer branding and Work Life Balance on Turnover Intention in Generation Z in Medan City: Job Satisfaction as Intervening. The population of this research is generation Z employees in Medan City. The number of samples used was 100 people with sampling techniques using purposive samples. While collecting data using questionnaires and documentation. The data analysis technique uses SmartPLS software. The results of the Outer Model Test show that all original sample indicator values are> 0.7, which means that all variable indicators used by researchers are declared valid. In addition, all statements from each variable are declared reliable which is characterized by a Cronbach's alpha value> 0.7, Composite reliability> 0.7 and Average Variance Extracted (AVE)> 0.5. While the results of the inner model test show Employer branding has a positive influence on Turnover Intention, that Employer branding has a positive influence on Job Satisfaction, Job Satisfaction has a negative effect on Turnover Intention, Worklife Balance has a negative influence on Turnover Intention, Sample = 0.558, T Statistics = 9.219 and P Values = 0.000. These results indicate that Work Life Balance has a positive influence on Job Satisfaction, Employer branding has a negative influence on Turnover Intention through Job Satisfaction, Job Satisfaction is able to mediate the relationship between Work Life Balance and Turnover Intention